Lipid Deprivation Induces a Stable, Naive-to-Primed Intermediate State of Pluripotency in Human PSCs - Cornacchia, Daniela (Cell Stem Cell, 2019)
Current challenges in capturing naive human pluripotent stem cells (hPSCs) suggest that the factors regulating human naive versus primed pluripotency remain incompletely defined. Here we demonstrate that the widely used Essential 8 minimal medium (E8) captures hPSCs at a naive-to-primed intermediate state of pluripotency expressing several naive-like developmental, bioenergetic, and epigenomic features despite providing primed-state-sustaining growth factor conditions. Transcriptionally, E8 hPSCs are marked by activated lipid biosynthesis and suppressed MAPK/TGF-β gene expression, resulting in endogenous ERK inhibition. These features are dependent on lipid-free culture conditions and are lost upon lipid exposure, whereas short-term pharmacological ERK inhibition restores naive-to-primed intermediate traits even in the presence of lipids. Finally, we identify de novo lipogenesis as a common transcriptional signature of E8 hPSCs and the pre-implantation human epiblast in vivo. These findings implicate exogenous lipid availability in regulating human pluripotency and define E8 hPSCs as a stable, naive-to-primed intermediate (NPI) pluripotent state.